Persistence of Biogeochemical Alterations of Deep‐Sea Sediments by Bottom Trawling. Issue 2 (18th January 2021) - Paradis, S.; Goñi, M.; Masqué, P.; Durán, R.; Arjona‐Camas, M.; Palanques, A.; Puig, P.
Abstract: Bottom trawling grounds have been expanding to deeper areas of the oceans since the mid‐XXth century, and mitigating strategies aimed to protect fish stocks, such as temporal trawling closures, have recently been implemented. Here we investigated the biogeochemical properties of sediment from a deep‐sea trawling ground in Palamós Canyon (NW Mediterranean) to assess the effects of a 2‐months trawling closure in the recovery of sedimentary organic matter. In comparison to untrawled areas, the continuous erosion and sediment mixing in trawling grounds led to coarser reworked sediments impoverished in organic carbon (∼30% loss) and promoted the degradation of labile compounds (52–70% loss). These impacts persisted after the temporal trawling closure, highlighting that this management strategy is insufficient to restore the seafloor. Considering the continuous expansion of bottom trawling grounds, this activity could have significant and irreversible biogeochemical impacts on ocean margins at a global scale, hampering their carbon burial capacity. Plain Language Summary: Bottom trawling grounds have been expanding to deeper areas of the oceans since the mid‐XXth century, causing substantial effects to fish populations. In order to reduce this impact, new management strategies have been introduced, such as establishing temporal trawling closures to allow fish populations to recover. Bottom trawling not only poses a threat to fish populations but also to the seafloor, since the continuous contact of trawling gear on the bottom erodes large volumes of sediment and reduces the amount and quality of organic matter. In this study, we assessed the effect of a 2‐months trawling closure in deep‐sea bottom trawling grounds in Palamós Canyon (NW Mediterranean) by collecting sediment samples in trawled and untrawled areas during different seasons. Our results show that sediment samples in the trawled site had substantially lower organic matter contents than in the untrawled site, and the remaining organic matter had poor nutritional quality. These impacts persisted after the temporal trawling closure, highlighting that this management strategy is insufficient to restore the seafloor. Considering the continuous expansion of bottom trawling grounds, this activity could have significant and irreversible impacts in organic matter available for benthic species in ocean margins at a global scale. Key Points: Bottom trawling disturbance on the deep seafloor depletes organic matter through erosion and degradation, hampering its preservation A 2‐month seasonal trawling closure is insufficient to restore the seafloor and it is estimated that it would take decades to recover Bottom trawling causes organic carbon losses from the seafloor comparable to those generated on land by tillage of agricultural fields